Measuring energy expenditure in narcolepsy using doubly labeled water and respiration chamber calorimetry - Donjacour, Claire E H M; Gool, Jari K; Schoffelen, Paul F; Wouters, Loek; Overeem, Sebastiaan; Lammers, Gert Jan; Pijl, Hanno; Westerterp, Klaas R (Sleep (New York, N.Y.), 2025)
Hypocretin deficiency causes type 1 narcolepsy, a condition characterized by excessive daytime sleepiness, cataplexy, and fragmented nocturnal sleep. Two-thirds of people with narcolepsy are also overweight, of which half are obese. The pathophysiology behind weight gain in people with narcolepsy remains unknown. We assessed a possible decrease in energy expenditure as a cause for overweight in narcolepsy using respiration chamber calorimetry and doubly labeled water. Ten males with type I narcolepsy and nine matched (for age, sex, and BMI) healthy controls were enrolled. Participants stayed in a respiration chamber for 24 hours. They subsequently received doubly labeled water and wore an accelerometer for 2 weeks to assess energy expenditure and physical activity under daily living conditions. Total daily energy expenditure, resting energy expenditure (REE), overnight metabolic rate, physical activity level, and activity-induced energy expenditure were measured. No significant differences were found in REE, mean 24-hour respiration chamber energy expenditure, overnight metabolic rate, and activity-induced energy expenditure when comparing people with narcolepsy type 1 to controls. Physical activity was also comparable between groups. Energy expenditure in narcolepsy type 1 is similar to matched controls, suggesting comparable metabolism and physical activity rates. It remains possible that metabolic changes are most pronounced around disease onset. In addition, patients had to discontinue their medication which may have influenced the results. Still, our findings suggest that other factors may also play a role in weight gain in narcolepsy, such as differences in dietary behavior.